2012
DOI: 10.1038/cgt.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical efficacy of the oncolytic measles virus expressing the sodium iodide symporter in iodine non-avid anaplastic thyroid cancer: a novel therapeutic agent allowing noninvasive imaging and radioiodine therapy

Abstract: Anaplastic thyroid cancer is an extremely aggressive disease resistant to radioiodine treatment because of loss of sodium iodide symporter (NIS) expression. To enhance prognosis of this fatal cancer, we validated the preclinical efficacy of measles virus (MV)-NIS, the vaccine strain of the oncolytic MV (MV-Edm), modified to include the NIS gene. Western blotting analysis confirmed that a panel of eight anaplastic thyroid cancer (ATC)-derived cell lines do not express NIS protein, but do express CD46, the MV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…There is a study that utilizes MV-Edm, which was modified to include the NIS gene to be combined with radiology treatment. This study demonstrated the oncolytic efficacy of MV-NIS in BHT-101 and KTC-3, ATC-derived cell lines and mouse model [87].…”
Section: Measles Virus -Preclinical and Clinical Studiesmentioning
confidence: 99%
“…There is a study that utilizes MV-Edm, which was modified to include the NIS gene to be combined with radiology treatment. This study demonstrated the oncolytic efficacy of MV-NIS in BHT-101 and KTC-3, ATC-derived cell lines and mouse model [87].…”
Section: Measles Virus -Preclinical and Clinical Studiesmentioning
confidence: 99%
“…83 Oncolytic viruses (measles, vaccinia, and lentiviruses) expressing the NIS gene have been used to induce cell death as well as facilitate noninvasive imaging and radioiodine therapy. 69,86,94 Combinatorial therapeutic options using small molecule inhibitors such as paclitaxel, 84 bevacizumab, 89 gancliclovir, 95 and aurora kinase inhibitor AZD1152, 82 along with independent virus treatments, have also been evaluated preclinically.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%
“…[66][67][68][69] In the recent past, a number of transgenic mice have been developed that mimic ATC in vivo [70][71][72][73] and serve as much more clinically relevant models for preclinical testing. These models have primarily been used to elucidate the hypothesis that ATCs arise as a progression from PTC or FTC due to hits to multiple signaling pathways and therefore provide the closest simulation environment reflective of direct in human testing.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%
See 2 more Smart Citations